On the dynamics of the critical Harper map - Datta, Sandip; Jäger, Tobias; Keller, Gerhard; Ramaswamy, R. (Nonlinearity, 2004)
We examine the behaviour of typical orbits in the Harper map, a quasiperiodically driven skew-product dynamical system in two dimensions. When the map is critical, namely when all Lyapunov exponents vanish, the dynamics is parabolic.
UnivIS-Import:2015-03-09:Pub.2004.nat.dma.pma29.onthed